Seismic vulnerability of circular tunnels in sand. Issue 11 (3rd November 2021) - de Silva, Filomena; Fabozzi, Stefania; Nikitas, Nikolaos; Bilotta, Emilio; Fuentes, Raul
Abstract : The paper is focused on the assessment of seismic fragility curves for circular tunnels under moderate to severe earthquakes with the aim of improving the reliability of the risk assessment of underground infrastructural networks. Non-linear two-dimensional dynamic analyses were performed on different tunnel and soil configurations by using the finite-difference method implemented in Flac2D software. The applied input motions were selected considering their amplitude and frequency content variability. The response accelerations and predominant frequencies computed at ground level, above the tunnel, were compared with the corresponding free-field results to distinguish the effects attributable to the tunnel presence from those due to the site amplification. Tunnel safety was assessed through fragility curves, taking into account the dependence of tunnel lining bending resistance on the axial force variation during the earthquake. The more effective intensity measure was investigated correlating the tunnel performance to peak ground accelerations and peak ground velocities computed at the ground level and at the bedrock depth, respectively. The resulting fragility curves showed a satisfying matching with the empirical ones, generated on the basis of the observed seismic damage on tunnels.